Synthesis and toxicity assessment of Coffea arabica extract-derived gold nanoparticles loaded with doxorubicin in lung cancer cell cultures - Trejo-Teniente, Isaí; Jaramillo-Loranca, Blanca Estela; Vargas-Hernández, Genaro; Villanueva-Ibáñez, Maricela; Tovar-Jiménez, Xochitl; Olvera-Venegas, Patricia Nayeli; Tapia-Ramírez, José (Frontiers in Bioengineering and Biotechnology, 2024)
Cancer is the second leading cause of death worldwide, despite the many treatments available, cancer patients face side effects that reduce their quality of life. Therefore, there is a need to develop novel strategies to increase the efficacy of treatments. In this study, gold nanoparticles obtained by green synthesis with Coffea arabica green bean extract were loaded with Doxorubicin, (a highly effective but non-specific drug) by direct interaction and using commercial organic ligands that allow colloidal dispersion at physiological and tumor pH. Conjugation of these components resulted in stable nanohybrids at physiological pH and a tumor pH release dependent, with a particle size less than 40 nm despite having the ligands and Doxorubicin loaded on their surface, which gave them greater specificity and cytotoxicity in H69 tumor cells.